ETHICAL PRACTICE OF TAX EVASION IN PERSONAL PERSPECTIVE : Study Of The Structuration Theory - Ni Putu Eka Widiastuti, - (IACSF, 2012)
The aim of this research is to explore of personal perspective on the ethics of tax evasion using the structuration theory which it is contributed by Anthony Gidden. The focuses of this research is in ethical judgment amonrg accountant and tax practitioner as human agents in a part of structure of an organization and as social system in part of the community. This paper begins with a review of the literature and identifies the main issues of tax evasion that become hot issues in Indonesia actually in 2010 until now. Qualitative method with postmodern approach is using to this research.Face-to-face interview to tax payer, tax consultant and tax administrative from the Directorate General of taxation. Interview divided in two parts to explore how they do their tax reports , manage the tax specially income tax and their opinion about the tax saving are some questions to tax payer and tax consultant, to tax administrative the focuses questions are about how facing taxpayers who want his tax payments as least as possible.As developing countries, Indonesia depends on tax in financing the whole development. The result of the research indicated that the whole informer consisting of tax payer , tax consultant and tax administrative said that because system of government that is not firmly make individuals in a organizational structure serves only the interests of his/her course , to tax payer feel do the act of tax evasion because there are disappointment with administration esp directorate general of taxation in which nearly all employees in this shows no sensorial living simplicity otherwise salary and their welfare derived from the people who pays taxes , to tax consultant because they hired by tax payer to do so that the interests of management tax client prioritized if it did not so consultant organization's structure in which it originated would regard not the service of clients , they do management tax but still make tax owed small by means deductible expense enlarged so as to a taxable income will be decreased and of course the tax paid is reduced. Tax officer ethics rules that do exist should be held firm in accordance with the professionalism of the Office but sometimes insistence on tax payer can not be denied especially if tax payer is a great company in Indonesia